ISOLATED GROWTH HORMONE DEFICIENCY - A RARE, BUT TREATABLE CAUSE OF LOW STATURE - Raluca Maria Vlad; Delia Irina Nicolaescu; Alice Ioana Albu (Amaltea Medical Publishing House, 2019)
Growth hormone deficiency is a rare cause of low stature. Early recognition of the disease results in effective treatment, leading to a final height as closely as possible to the genetic target. The authors present the case of a 1 year 2 months old girl admitted for growth evaluation in our department. She had been previously diagnosed with isolated growth hormone deficiency in an Endocrinology Unit and was now sent to complete the investigations and undergo imaging studies. The laboratory investigations excluded other pathologies. The MRI showed adenohypophysis hypoplasia, thin hypophyseal stalk. Se is started on growth hormone substitution treatment with good results.